Students' behavioural engagement in reviewing their tele-consultation feedback within an online clinical communication skills platform. (May 2019) - Liu, Chunfeng; Lim, Renee; Taylor, Silas; Calvo, Rafael A.
Abstract: The benefit of reviewing personal feedback to students' learning of clinical communication skills is well researched. Less is known about the factors that related to students' engagement in reviewing non-compulsory online feedback, and ways to motivate their behavioural engagement. In this paper, we reported two studies in which medical students completed assessed clinical video conferencing consultations with human simulated patients via an online training platform that also provided automated and human feedback for students. In Study 1, three days after the consultation, an email with different instructional styles (autonomy-supportive, controlling or control) was sent to different groups reminding students to review their feedback. In Study 2, up to three repetitions of the same, either autonomy-supportive or controlling, emails were sent to students. Results of Study 1 revealed that students who reviewed feedback before receiving emails achieved higher assessment results and reported higher degree of autonomy to participate in the training program than the remaining students. However, the different instructional styles of the single email in this study did not significantly influence the students' engagement differently. Study 2 results revealed that students who received controlling emails displayed higher engagement than students who received autonomy-supportive emails. Findings suggested that multiple factors might influence students' engagement in reviewing their online feedback, and this study provided evidences of the effects of using emails to motivate students to review the feedback. Highlights: Students showing higher engagement achieved higher assessment results. More highly engaged students demonstrated more autonomy in their learning. Multiple controlling instructional emails had greatest impact on students' engagement.